PENGARUH STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA PEGAWAI DINAS PENGELOLAAN SUMBER DAYA AIR KABUPATEN WAJO - Mursida Abu (P3M STIEM BONGAYA, 2019)
Stress and conflict are two things that often happens in organizational life. Both can be a determinant of employee performance improvement in organizations. Stress will be increased where emotional condition or physiological reaction that occurs in situations where employees feel a threat to it’s objectives are important thinks that may not be achieved. Thus increasing a conflict within the employee. Namely the existence of discrepancies with the objectives to be achieved and in contrast to the expectations of employees, causing a turmoil that resulted in employee performance. So the company should be able to know how to encourage stress and conflict in order to generate positive and how to cope with stress and conflict occurs when a negative thing. The analytical method used in this research is multiple linear regression analysis. The results of partial stress and conflict have a significant effect on performance.